Electrochemical investigation of urea oxidation reaction on β Ni(OH)2 and Ni/Ni(OH)2. (10th July 2018) - Singh, Ramesh Kumar; Schechter, Alex
Abstract: Urea oxidation is the key limiting reaction in energy conversion devices based on this molecule. Ni-based catalysts are widely used to catalyze this reaction via the intermediate formation of reactive NiOOH from nickel hydroxide. In this study, β Ni(OH)2 urea oxidation activity is compared to that of Ni/Ni(OH)2 . Electrochemical active surface area, exchange current density, rate constant, and capacitance are estimated for these catalysts to mechanistically probe the reaction. A quantitative electrochemical analysis of urea oxidation on these catalyst surfaces yields important reaction parameters. The reaction orders of β Ni(OH)2 with respect to KOH and (NH2 )2 CO are 1.22 and 0.26, respectively, at a kinetically-controlled potential of 1.43 V vs. RHE. The reaction order with respect to KOH decreases gradually with potential and it is almost constant with urea. The similar trends in reaction order are observed with Ni/Ni(OH)2 . Electrochemical impedance measurements displayed lower charge-transfer resistance of β Ni(OH)2 indicative of faster urea oxidation kinetics. It is observed that at the potential of 1.43 V, the charge transfer resistance of β Ni(OH)2 (87.3 Ω cmECSA 2 ) lowered by a factor of ∼1.23 compared to Ni/Ni(OH)2 (107.6 Ω cmECSA 2 ). The electrochemical surface area normalized heterogeneous rate constant of β Ni(OH)2 is ∼2 times higher than that of Ni/Ni(OH)2, in line their high intrinsic urea oxidation activity, capacitance and higher electrochemical phase stability. Moreover, the electrochemical chemical mechanism is observed on both catalysts in support with earlier report [1 ].